2016
DOI: 10.1039/c6ra21436c
|View full text |Cite
|
Sign up to set email alerts
|

Silanization induced inherent strain in graphene based filler influencing mechanical properties of polycarbonate urethane nanocomposite membranes

Abstract: Nanosheet type fillers apart from their size and surface functional groups may have numerous attributes affecting the mechanical properties of polymeric nanocomposites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Adhesion molecules are also important in the regeneration of nerves as exemplified by SCs, secreting adhesion molecules in their natural milieu that promotes neural regeneration and remyelination . Graphene (G), a two-dimensional nanomaterial with its unique inherent properties, has found several applications, involving neural cell adhesion, regeneration, and in improving cell–material interactions . Thin sheets of graphene oxide (GO) derived from oxidation and exfoliation of graphite are a biocompatible entity that has the potential to mediate cell adhesion and differentiation for tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Adhesion molecules are also important in the regeneration of nerves as exemplified by SCs, secreting adhesion molecules in their natural milieu that promotes neural regeneration and remyelination . Graphene (G), a two-dimensional nanomaterial with its unique inherent properties, has found several applications, involving neural cell adhesion, regeneration, and in improving cell–material interactions . Thin sheets of graphene oxide (GO) derived from oxidation and exfoliation of graphite are a biocompatible entity that has the potential to mediate cell adhesion and differentiation for tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] In the case of graphene oxide, which is a rather economical (though non-conductive) alternative of graphene, a major problem as nanoller is the lack of interfacial bonding with the polymer matrix (due to its high hydrophilicity), therefore leading to poor dispersion and agglomeration of the nanosheets. [13][14][15] Nevertheless, GO has a vast amount of reactive functional groups, such as hydroxyl, epoxy, and carbonyl groups, [16][17][18][19][20] which provide reactive sites for surface modifying the nanosheets to tailor specic properties, such as enhancing their compatibility with polymer matrices. 15,21 Even though different surface modication techniques in GO have been previously explored, [22][23][24][25] in this work we take advantage of the high reactivity of alkylamines to modify the surface of GO.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the characteristics of GO and PU, nanocomposites based on these materials are strong candidates to be used in biomedical devices when mechanical strength is required without drastically reducing the original flexibility of the matrix. Very few articles have been dedicated to the study of nanocomposites based on PCU and GO, however, the articles found in the specialized literature are dedicated to the use of high content of fillers or do not assess the real influence of the GO in the morphological structure of the segments present in the PCU and its consequences on mechanical and/ or themal properties of the nanocomposites 32,33 . The main goal of this work is to evaluate the impact on thermo and thermomechanical properties as well as the tensile properties of a soft formulation of medical grade poly(carbonate urethane) (PCU) when two distinct GOs with different levels of oxidation and morphology (number of layers and lateral size) are added using the solution blending process.…”
Section: Introductionmentioning
confidence: 99%